Short Play Approach for Analytical Chemistry Class - Mohd Dzul Hakim Wirzal; Nur Syakinah Abd Halim (ASEAN Journal of Science and Engineering Education, 2022)
In this era, cooperative learning strategies have been practiced extensively as an alternative to conventional teaching methods. This is because some of the conventional methods are no longer suitable to be applied to the younger generation.  Cooperative learning strategies such as role-play for instance are recommended in nurturing the exciting vibe of learning in class while at the same time boosting the students’ confidence level. In this case study, a total of 106 students in the 3rd Year in the 2nd Semester under the Chemical Engineering Department of Universiti Teknologi PETRONAS were involved in a short-play approach for the subject of Analytical Chemistry. It is found that the short-play approach effectively improved the basic understanding of students towards the Analytical Chemistry subject. Furthermore, the majority of the students also scores better in the final exam as compared during the test.